The Hidden Face of Urban Slavery A Look at the Coartados Rental Market - Varella, Claudia; Barcia, Manuel (University Press of Florida, 2022)
The Hidden Face of Urban Slavery A Look at the Coartados Rental Market In 1845, the Cuban Junta de Fomento, seeing an escalating crisis develop in front of their own eyes, complained that “infinite [numbers],” of coartados had wound up in the judicial slave depósitos.1 Although the Real Consulado was supposed to act as a protector of slaves for the duration of their temporary stay while their lawsuits or ownership conflicts were being resolved, in reality all too often it failed to do so.2 Instead, following the example of the evolving role of the Casa de Beneficencia, the institution in charge of taking care of orphans in Havana since 1792, the Real Consulado took advantage of the situation and benefited financially from it. Its depósitos even had the ability to speculate with the fees they charged for hiring slaves, making no distinction whatsoever between “full” slaves and coartados, and without protecting the coartados or giving them any special treatment. With that attitude, the Real Consulado violated not only the relevant appendix to Valdés’s regulations of 1842, but also the very agreement signed between them and the Casa de Beneficiencia for the sub-hiring of coartados.3 Understanding the urban rental market is crucial if we are to grasp the multiple ways in which coartados were forced to react to new damaging scenarios , as the ones exposed above. As new changes to the urban rental market came into existence and as their impact on the slavery-based service sector expanded, coartados found themselves often trapped in what can only be described as a buyer-to-buyer dynamic, which forced them to go from one master to another, almost always against the wishes of those who owned them, and frequently against their own wishes too.
Keywords: urban slavery; rental market; coartados; WOS(2)